Collaborative innovation blocs and antifragility - Niklas Elert; Magnus Henrekson (Research Institute of Industrial Economics (IFN), 2019)
We present the theory of the collaborative innovation bloc (CIB), an evolving system of innovation within which activity takes place over time. We show how the application of the CIB perspective can help make institutional and evolutionary economics more concrete, relevant, and persuasive, especially regarding policy prescriptions. Such policy actions should strive to improve the antifragility of CIBs and the economic system as a whole, thus enabling individual CIBs and the broader economic system to thrive when faced with macroeconomic shocks. With this in mind, we develop heuristics to evaluate antifragility at the micro, meso, and macro levels before identifying a set of institutional areas where reform can be undertaken to improve antifragility.
Keywords: D20; G32; L23; L26; O33; 330; Evolutionary economics; Institutional Economics; Entrepreneurship; Innovation; Institutions